Biomolecular Profiling by MALDI-TOF Mass Spectrometry in Food and Beverage Analyses - Šebela, Marek (International journal of molecular sciences, 2022)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has frequently been applied to the analysis of biomolecules. Its strength resides not only in compound identification but particularly in acquiring molecular profiles providing a high discriminating power. The main advantages include its speed, simplicity, versatility, minimum sample preparation needs, and a relatively high tolerance to salts. Other benefits are represented by the possibility of automation, high throughput, sensitivity, accuracy, and good reproducibility, allowing quantitative studies. This review deals with the prominent use of MALDI-TOF MS profiling in food and beverage analysis ranging from the simple detection of sample constituents to quantifications of marker compounds, quality control, and assessment of product authenticity. This review summarizes relevant discoveries that have been obtained with milk and milk products, edible oils, wine, beer, flour, meat, honey, and other alimentary products. Marker molecules are specified: proteins and peptides for milk, cheeses, flour, meat, wine and beer; triacylglycerols and phospholipids for oils; and low-molecular-weight metabolites for wine, beer and chocolate. Special attention is paid to sample preparation techniques and the combination of spectral profiling and statistical evaluation methods, which is powerful for the differentiation of samples and the sensitive detection of frauds and adulterations.
Keywords: marker; Cheese; food; classification; Oils; mass spectrometry; reprodukovatelnost výsledků; oleje; Reproducibility of Results; protein; sýr; adulteration; Animals; oil; zvířata; differentiation; mléko; milk; MALDI; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Milk